PERANCANGAN SISTEM INFORMASI PENJUALAN MOTOR SECOND BERBASIS WEB: DESIGN OF WEB-BASED SECOND MOTORCYCLE SALES INFORMATION SYSTEM - Delia Meldra (Engineering and Technology International Journal, 2020)
This study aims to design a dashboard that can help companies on CV. Restu Motor Jl. Tiban Indah Permai No. 5, Sekupang, Batam. Because there is no system that displays information related to the work done and completed by the company admin, so a dashboard design is needed. Data on the dashboard system is obtained from motorcycle sales data which consists of cashier data to print proof of payment if there is a sale, motorcycle collection data along with the purchase price and selling price, sales data along with profit/profit data. By using the PHP programming language and using MySQL as a database. Qualitative research techniques, by collecting data and information descriptively. The results of this study display a text-shaped dashboard consisting of cashiers, motorcycle data, sales data, target percentages, it is hoped that this dashboard can help companies analyze and control sales.